Adverse birth outcome: a comparative analysis between cesarean section and vaginal delivery at Felegehiwot Referral Hospital, Northwest Ethiopia: a retrospective record review [Corrigendum] - Abebe Eyowas F; Kidane Negasi A; Eyassu Aynalem G; Gebeyehu Worku A; Dadi AF (Dove Medical Press, 2016)
Abebe Eyowas F, Negasi AK, Aynalem GE, Worku AG. Pediatric Health, Medicine and Therapeutics. 2016;7:65–70On page 65 Abel Fekadu Dadi should have been listed as an author. The incorrect author list was:Fantu Abebe Eyowas1Ashebir Kidane Negasi1Gizachew Eyassu Aynalem1Abebaw Gebeyehu Worku2The correct author list should have been:Fantu Abebe Eyowas1Ashebir Kidane Negasi1Gizachew Eyassu Aynalem1Abebaw Gebeyehu Worku2Abel Fekadu Dadi2Read the original article